Acute perforated transverse colon diverticulitis simulating acute cholecystitis: case report and literature review - Chavez, Alberto Manuel Gonzalez; Vazquez, Alain Garcia; Hernandez, Diego Abelardo Alvarez; Chavez, Mario Andres Gonzalez; Blanco, Ricardo Ray Huacuja; Delgado, Jose Miguel Ramos (International Surgery Journal, 2017)
Transverse colon diverticulitis is a rare entity, described for the first time in 1944 by Thompson and Fox. Even more uncommon if presented with diverticular perforation of the colon. When ranking diverticula distribution by their anatomical location site, it has been set up that transverse colon is involved in an average of 10% of the cases, but diverticulitis or inflammation of these sacculations in this anatomical region only occurs in 0.5-2.5% of the cases. Female, 44 years old, who came to emergency room with acute abdominal pain as colic of 24 hours of evolution, Acute cholecystitis was considered as a first diagnostic possibility. Pain persistence and peritoneal irritation lead to an abdominal contrasted tomography (contrast IV). Oval formations protruding from the gut lumen in ascending and transverse colon were found, corresponding to diverticula. Patient was admitted in hospital and maintained in fasting period and with a double antibiotic scheme she was discharged on the 5th day of hospital stay. Transverse colon diverticulitis is a rare entity, there exist less than 50 cases reported in worldwide literature but it has been determined that patients with transverse colon diverticulitis are 15 and 20 years younger than patients with left colon diverticulitis. That is, average age of manifestation is about 45 years old. 85% of the cases have been described in women. Reports managed it successfully with antibiotics. The present report could be achieved favourably with a double antibiotic scheme, with no need of surgery.